RESPONSIBLE AND SOLIDARITY TOURISM, APPROACH TO ITS THEORETICAL FRAMEWORK AND CONNECTIONS WITH THE TOURIST INTELLIGENCE - Javier Perogil (Revista Iberoamericana de Economía Solidaria e Innovación Socioecológica, 2018)
This article is dedicated to the study of two new concepts that have appeared in the tourism sector in the recent decades, they are the so-called responsible tourism and solidarity tourism, both of them have moral ethical references in the specific business of tourism, in which the desire to commercialize also seems to place the good will that tourists contemplate in their own trips.  In this document, first of all, an approach to the solidarity economy is made as a possible reference to the tourism framework studied. Secondly, a theoretical and referential revision of both concepts is developed; with the idea of contrasting, analyzing and assessing the different perspectives from which they are viewed. And third and last, the connection of responsibility and solidarity in its application to tourism with a new stream of destination management, Tourist Intelligence, is considered.